FDI and Growth: Can different regional identities shape the returns to foreign capital investments? - Laura Resmini; Laura Casi (European Regional Science Association (ERSA), 2014)
Do regional identities determine different levels of FDI-induced growth? This paper analyses the impact of FDI on the growth rates of European regions. In so doing, it discusses the role of different components of territorial capital in magnifying or daunting such an impact. The paper starts from a very simple theoretical framework that clarifies how territorial capital can shape the returns to foreign direct investments. The subsequent empirical analysis uses data from the European Value Study to identify 3 soft components of territorial capital that define the identity of a region and can be relevant in shaping the impact of foreign capital on local growth. Using data from Eurostat and FDIregio database, the paper studies the impact of FDI induced spillovers on regional growth in European regions, controlling for possible endogeneity. Results indicate that technological spillovers are an important source of regional growth, but they take place only if the level of trustworthiness/generalized morality is widespread in the region, supporting the idea that low free-riding attitudes increase efficiency of transaction and effectiveness of cooperation between multinational and the regional economic system. The effect of relational capital is more ambiguous. A more disaggregated analysis reveals that some effects vary depending on the origin (intra vs extra European FDI) and on the type of economic activity (manufacturing vs service FDI).
Keywords: F23; O18; O52; 330; FDI; regional growth; territorial capital